KEPEMIMPINAN KEPALA SEKOLAH BERDASARKAN KECERDASAN EMOSIONAL DI SEKOLAH MENENGAH PERTAMA ISLAM TERPADU AMSAR TAHUN PELAJARAN 2023/2024 - HAFIDZ ANSHORI Hafidz (UNISAN JURNAL, 2024)
Abstract: Emotional Intelligence is one point of view that is able to analyze the leadership of a school principal. The aim of this research is to examine the leadership of school principals based on their emotional intelligence. The Principal's leadership based on emotional intelligence is considered very good. This has a positive impact on the sustainability of the organization's foundation. This research is a type of qualitative research with a descriptive nature that will describe and describe research data using data pole analysis. The results of the research found that the ability of the Principal of Amsar Integrated Islamic Middle School to carry out primal leadership was very good. This is proven based on triangulation of data and sources. The principal of Amsar Integrated Islamic Middle School has a high commitment to his vision for the future, especially during stressful times or in the midst of increasing responsibilities. The head of the Amsar Integrated Islamic Middle School as a form of leadership based on emotional intelligence is considered good. The principal always pays attention to the welfare of teachers, pays attention to the quality and continuity of learning both at school and in Islamic boarding schools. The principal takes an emotional approach to all residents in the school environment. This really helps the Principal in understanding the problems faced both in terms of planning, organizing, implementing and supervising the organization as an institution that oversees education.